Regulating Business by Independent Commission - Bernstein, Marver H. (Book collections on Project MUSE., 1955)
A critical examination of the role of the independent regulatory commissions, attempting to develop a more realistic concept of the process of governmental regulation and to appraise the independent commission as an agent of governmental regulation at the national level. Originally published in 1955. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.